CO2 emissions and geochemistry from geothermal systems in Iceland - Jowita Wiktoria Loboda 1996- (2024)
High-temperature geothermal systems in Iceland are primarily located along the on- land section of the mid-Atlantic ridge (MAR). These geothermal systems are dominantly hosted in mafic (basaltic) crust, however silicic lithologies are not uncommon. Based on the location and stable isotope systematics of the reservoir fluids, the mantle has been previously recognized to be the dominant source of CO2 in fluids of geothermal systems in Iceland. The reported CO2 concentration of geothermal fluids range from 0.050 to 599 mmol/kg. Aquifer chemical compositions for these fluids were calculated from surface and steam phases discharge data using the WATCH speciation program. To investigate further controls on the CO2 content of geothermal fluids the effects of rock-fluid-gas interaction were investigated using the PHREEQC reaction path stimulation program to achieve a better understanding of the ongoing processes and behavior of CO2 and CO2 fluxes within the high-temperature geothermal systems in Iceland. The results from the geochemical modelling showed that CO2 concentrations and temperature together with host rock lithology may be considered to be the main factors influencing CO2 fluxes. It is due to associated depressurization boiling convergence with dominant process of two-phase vapor fractioning, which results in depletion of CO2 in the fluid and rising the initial pH value. Therefore, the initial pH value is an important factor over regulating dissociation of C-species in the fluids, which in turns may lead to potential extent of CO2 uptake into carbonate formation. Subsequently, the readiness of host rocks rich in Mg and Ca reactants results in high carbonate formation, thus in depletion of CO2 concentration in ascending fluid. Thereby, progressive boiling results in earlier partition of CO2 into the vapor phase and minimal boiling in the systems experience only limited CO2 partitioning into the vapor phase. However, it needs to be noted that the fluid CO2 concentration and fluxes of the geothermal systems may ...